Flame-retardant waterproof coiled material and preparation method thereof

By using MOF@hexagonal boron nitride@phytic acid as a modified flame retardant, combined with polysiloxane coating technology and fiber filler, the problem of improving the flame retardant performance of flame retardant waterproof coils in the prior art is solved, and the problem of improving the flame retardant performance of flame retardant waterproof coils in the prior art is achieved. Efficient flame retardant effect and mechanical properties improvement.

CN119320529AActive Publication Date: 2025-01-17CHENGDU SAITE WATERPROOF MATERIAL CO LTD

Patent Information

Application Number
CN202411540720.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-17
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

When the existing flame retardant waterproof coils improve flame retardant performance, it is difficult to evenly disperse the inorganic flame retardant agent, resulting in poor flame retardant effect, and organic flame retardant is prone to migration, affecting material performance.

Method used

MOF@hexagonal boron nitride@phytic acid as a modified flame retardant, and through hydrothermal reaction and polysiloxane coating technology, a modified flame retardant was prepared, and the material performance was improved with fiber fillers.

Benefits of technology

It significantly improves the flame retardant effect and mechanical properties of the flame retardant waterproof coil, solves the problems of poor dispersion of inorganic flame retardant and migration of organic flame retardant, and improves the stability and durability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112729680000081
    Figure BDA0005112729680000081
Patent Text Reader

Abstract

The invention relates to the technical field of waterproof coiled materials, and discloses a flame-retardant waterproof coiled material and a preparation method thereof.The flame-retardant waterproof coiled material is prepared from, by weight, 100 parts of thermoplastic polyolefin elastomer, 20-40 parts of modified flame retardant, 5-18 parts of fiber filler, 0-3 parts of lubricant, 0-3 parts of antioxidant, 0-3 parts of stabilizer and 0-15 parts of pigment; the modified flame retardant takes MOF, hexagonal boron nitride and phytic acid as an inner core, and polysiloxane is cross-linked and polymerized on the surface of the inner core. According to the flame-retardant waterproof coiled material provided by the invention, if the MOF or the modified MOF material is independently added into the resin material, the problem of poor compatibility of the MOF or the modified MOF material and the resin system cannot be avoided. According to the invention, a microcapsule technology is creatively utilized to polymerize polysiloxane on the surface of the MOF material, so that not only can the problem of dispersion of the MOF material be effectively solved, but also the compatibility of polysiloxane and the flame-retardant characteristic of organic silicon are utilized to promote formation of carbon at high temperature by utilizing phosphorus, and the thermal stability of a carbon layer is improved by utilizing silicon; therefore, the purpose of synergistic flame retardance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waterproof coiled materials, in particular to a flame retardant waterproof coiled material and a preparation method thereof. Background Art

[0002] At present, as people attach great importance to building safety, the demand for flame retardant waterproof membrane is increasing, especially in commercial buildings and public facilities. Flame retardant waterproof membrane is a building material with both waterproof and flame retardant properties. It is mainly used in building roofs, basements, etc. to prevent moisture penetration while improving the fire safety of buildings.

[0003] Flame-retardant waterproofing membranes mainly include polyvinyl chloride (PVC) waterproofing membranes, ethylene propylene diene monomer (EPDM) waterproofing membranes, thermoplastic polyolefin (TPO) waterproofing membranes, etc. Among these membranes, PVC waterproofing membranes contain plasticizers, which are prone to release harmful substances due to the migration of plasticizers; EPDM waterproofing membranes have high processing requirements. TPO waterproofing membranes are widely used because they do not contain plasticizers and have the characteristics of strong weather resistance, good mechanical properties, pollution resistance, and easy processing.

[0004] It is imperative to improve the fire safety of buildings, which is related to property and life safety. Based on this, the flame retardancy of TPO waterproof membrane needs to be further improved. In the direction of improving flame retardant performance, in the prior art, there are currently ways to improve flame retardant performance by adding inorganic flame retardants, organic flame retardants, and organic-inorganic synergistic flame retardant; among them, the synergistic improvement of flame retardancy between multiple flame retardants is the current main improvement method, such as patents with publication numbers CN103242582A, CN117659882A, CN112694673A, and CN115746447A. The aforementioned patents are all prepared by blending multiple flame retardants in the system, and the degree of improvement in flame retardant performance is not high. The reason is that when inorganic flame retardants are added to the polymer (or resin) system, they are easy to agglomerate. In the resin mixed system, it is easy to be difficult to disperse evenly due to different chemical properties, which makes the flame retardant effect poor, resulting in the problem of poor mechanical properties of the material. At the same time, organic flame retardants such as some small molecule flame retardants are prone to migration, thus affecting the flame retardant properties of the material. Summary of the invention

[0005] Technical problems solved by the present invention:

[0006] In view of the shortcomings of the prior art, a flame retardant waterproof coiled material and a preparation method thereof are provided.

[0007] The technical solution adopted by the present invention is:

[0008] In view of the above technical problems, an object of the present invention is to provide a flame retardant waterproof coiled material and a preparation method thereof.

[0009] Based on this, the specific implementation plan is:

[0010] A flame retardant waterproof coiled material, wherein the raw material components are calculated by weight and include 100 parts of a thermoplastic polyolefin elastomer, 20-40 parts of a modified flame retardant, 5-18 parts of a fiber filler, 0-3 parts of a lubricant, 0-3 parts of an antioxidant, 0-3 parts of a stabilizer, and 0-15 parts of a pigment; the modified flame retardant is a polysiloxane cross-linked on the surface of the core with MOF@hexagonal boron nitride@phytic acid as the core.

[0011] In the present invention, the preparation method of the modified flame retardant comprises the following steps:

[0012] In the first step, zirconium tetrachloride and 2-aminoterephthalic acid are subjected to hydrothermal reaction, and then hexagonal boron nitride is added to continue the reaction to obtain intermediate I;

[0013] In the second step, the intermediate I is dispersed, phytic acid is added, and the intermediate II is obtained by treatment;

[0014] In the third step, intermediate II is treated with HDTMS to obtain intermediate III;

[0015] In the fourth step, after the intermediate III, octamethylcyclosiloxane, tetramethylammonium hydroxide and tetrahydrofuran are reacted, acetic acid and hexamethyldisiloxane are added to continue the reaction, and then low-boiling substances are removed by vacuum to obtain a modified flame retardant.

[0016] Furthermore, zirconium tetrachloride and 2-aminoterephthalic acid are reacted in a molar ratio of 1:1, the mass ratio of zirconium tetrachloride to hexagonal boron nitride is 1:1; the ratio of intermediate I to phytic acid is 1.5 g:5 mL; the mass ratio of intermediate II to HDTMS is 1:1; the mass ratio of intermediate III, methylcyclosiloxane, tetramethylammonium hydroxide, tetrahydrofuran, acetic acid, and hexamethyldisiloxane is 30:100:10:5:5:15.

[0017] To expand, the specific preparation method is as follows:

[0018] In the first step, zirconium tetrachloride is dissolved in DMF, and then 2-aminoterephthalic acid is added and stirred, and then glacial acetic acid is added, placed in a hydrothermal reactor, and reacted at 120°C for 2h, and then hexagonal boron nitride nanosheets are added, stirred evenly, and then reacted at 120°C for 20h. After the reaction is completed, it is washed with ethanol several times and dried to obtain MOF@hexagonal boron nitride material. In the above, zirconium tetrachloride and 2-aminoterephthalic acid react in a molar ratio of 1:1, and the mass ratio of zirconium tetrachloride to hexagonal boron nitride is 1:1.

[0019] In the second step, the MOF@hexagonal boron nitride material is dispersed in deionized water, and the phytic acid solution (the volume ratio of phytic acid to deionized water is 1:4) is added thereto, and the mixture is stirred for 6 hours at 30°C, washed with deionized water several times, and dried to obtain the MOF@hexagonal boron nitride@phytic acid material. In the above, the ratio of MOF@hexagonal boron nitride to phytic acid is 1.5 g:5 mL.

[0020] The third step is to disperse the obtained MOF@hexagonal boron nitride@phytic acid material in an ethanol aqueous solution (V 乙醇 :V 水 =1:2) to obtain a reaction solution, and adjust the pH value of the reaction solution obtained above to 10, then drop the modified solution into the reaction solution, and stir the reaction at room temperature for 12 hours, then wash with ethanol several times, and dry to obtain the modified MOF@hexagonal boron nitride@phytic acid. In the above, the modified solution is an ethanol aqueous solution of HDTMS (V 乙醇 :V 水 =3:7), the mass ratio of MOF@hexagonal boron nitride@phytic acid to HDTMS is 1:1.

[0021] In the fourth step, the modified MOF@hexagonal boron nitride@phytic acid, octamethylcyclosiloxane, tetramethylammonium hydroxide, and tetrahydrofuran are uniformly mixed, heated to 85°C, reacted for 5 hours, and then acetic acid and hexamethyldisiloxane are added thereto, and the reaction is continued for 1 hour, and then the temperature is raised to 150°C and low-boiling substances are removed by vacuum for 2 hours to obtain a modified flame retardant. In the above, the mass ratio of modified MOF@hexagonal boron nitride@phytic acid, octamethylcyclosiloxane, tetramethylammonium hydroxide, tetrahydrofuran, acetic acid, and hexamethyldisiloxane is 30:100:10:5:5:15.

[0022] In the present invention, the thermoplastic polyolefin elastomer comprises polyolefin (at least one of PP and PE) and elastomer (at least one of EPDM, NBR, IIR and NR). The mass ratio of polyolefin to elastomer is 7:3.

[0023] In the present invention, the fiber filler includes at least one of glass fiber and carbon fiber. When the fiber filler is added to the resin system, it needs to be treated with silane coupling agent KH550 first, and the treatment method can be conventional, the purpose is to improve the compatibility with the resin system.

[0024] In the present invention, the antioxidant includes at least one of antioxidant 1010 and antioxidant 1076 .

[0025] In the present invention, the stabilizer is a light stabilizer, specifically UV531.

[0026] In the present invention, the pigment includes at least one of titanium dioxide and carbon black.

[0027] In the present invention, the lubricant is stearic acid or a stearate.

[0028] The technical mechanism and beneficial effects adopted by the present invention are as follows:

[0029] (1) The flame retardant waterproof roll provided by the present invention uses a modified flame retardant prepared by using MOF material and polysiloxane and is applied to the flame retardant waterproof roll, which can have the advantages of both mechanical properties and flame retardant properties.

[0030] (2) The flame retardant waterproof coiled material provided by the present invention integrates the above two together in the form of a modified flame retardant in a core-shell form, which can give full play to the advantages of both, thereby synergistically improving the flame retardant effect.

[0031] (3) The flame retardant waterproof coiled material provided by the present invention uses MOF material as a flame retardant. The rigid skeleton, high specific surface area, heat resistance and other properties provided by it can significantly improve the flame retardant effect. However, if MOF material is added alone, its improvement effect is limited. Therefore, by introducing hexagonal carbon nitride and phytic acid into MOF material, that is, introducing nitrogen and phosphorus elements into it, the purpose of improving the flame retardant effect is achieved. At the same time, if hexagonal boron nitride is added alone, it is easy to cause accumulation and aggregation, thereby resulting in the problem of poor flame retardant effect.

[0032] (4) The flame retardant waterproof coiled material provided by the present invention, if MOF or modified MOF material is added to the resin material alone, will inevitably cause the problem of poor compatibility with the resin system. Based on this, we creatively use microcapsule technology to polymerize polysiloxane on the surface of MOF material, which can not only effectively solve the problem of MOF material dispersion, but also use the compatibility of polysiloxane and the flame retardant properties of organic silicon (generating a silicon-carbon isolation layer to isolate oxygen), as well as using phosphorus to promote the formation of carbon at high temperature and silicon to enhance the thermal stability of the carbon layer, so as to achieve the purpose of synergistic flame retardancy.

[0033] (5) The flame-retardant waterproof roll provided by the present invention is mixed with fiber fillers (carbon fiber, glass fiber) to improve the tensile strength and puncture resistance of the roll, and improve the stability and durability of the roll. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0035] The preparation process of the modified flame retardant includes the following operations:

[0036] In the first step, 0.45g zirconium tetrachloride was dissolved in 100mL DMF, and then 0.35g 2-aminoterephthalic acid was added and stirred, and then 5mL glacial acetic acid was added, placed in a hydrothermal reactor, and reacted at 120°C for 2h, and then 0.45g hexagonal boron nitride was added, stirred evenly, and then reacted at 120°C for 20h. After the reaction was completed, it was washed with ethanol several times and dried to obtain MOF@hexagonal boron nitride material.

[0037] In the second step, 1.5 g of MOF@hexagonal boron nitride material was dispersed in 100 mL of deionized water, 25 mL of phytic acid solution (the volume ratio of phytic acid to deionized water was 1:4) was added thereto, and the mixture was stirred continuously at 30°C for 6 h, and then washed with deionized water several times and dried to obtain MOF@hexagonal boron nitride@phytic acid material.

[0038] In the third step, 1 g of the obtained MOF@hexagonal boron nitride@phytic acid material was dispersed in 150 mL of ethanol aqueous solution (V 乙醇 :V 水 =1:2) to obtain a reaction solution, and adjust the pH value of the reaction solution obtained above to 10 (here, it can be adjusted with ammonia water), and then add the modified solution (1wt% HDTMS ethanol aqueous solution, wherein V 乙醇 :V 水 =3:7, 1 g of HDTMS is sufficient) was dropped into the aforementioned reaction solution, and the mixture was stirred for reaction at room temperature for 12 h. The mixture was washed with ethanol for several times and then dried to obtain the modified MOF@hexagonal boron nitride@phytic acid.

[0039] In the fourth step, the modified MOF@hexagonal boron nitride@phytic acid, octamethylcyclosiloxane, tetramethylammonium hydroxide, and tetrahydrofuran are uniformly mixed, heated to 85°C, reacted for 5 hours, and then acetic acid and hexamethyldisiloxane are added thereto, and the reaction is continued for 1 hour, and then the temperature is raised to 150°C and low-boiling substances are removed by vacuum for 2 hours to obtain a modified flame retardant. Among them, the mass ratio of modified MOF@hexagonal boron nitride@phytic acid, octamethylcyclosiloxane, tetramethylammonium hydroxide, tetrahydrofuran, acetic acid, and hexamethyldisiloxane is 30:100:10:5:5:15.

[0040] Example 1

[0041] The present embodiment provides a waterproof and flame-retardant coiled material, the raw materials of which are specifically 100 parts of thermoplastic polyolefin elastomer (7:3 of PP and EPDM), 30 parts of the modified flame retardant prepared above, 10 parts of glass fiber treated with KH550, 1.5 parts of stearic acid, 1 part of antioxidant 1010, 1.5 parts of light stabilizer UV531, and 1 part of titanium dioxide.

[0042] The raw materials of each component are weighed according to the above-mentioned proportion, and after being uniformly stirred, they are extruded and granulated by a twin-screw extruder, and then extruded (200° C., 2.5 m / min), calendered, shaped, and rolled to obtain a flame-retardant waterproof membrane.

[0043] Example 2

[0044] The difference between this embodiment and embodiment 1 is that the raw material components of the coil are different.

[0045] Specifically, 100 parts of thermoplastic polyolefin elastomer (7:3 PP and EPDM), 25 parts of the modified flame retardant prepared above, 15 parts of glass fiber treated with KH550, 1.5 parts of stearic acid, 1 part of antioxidant 1010, 1.5 parts of light stabilizer UV531, and 1 part of titanium dioxide.

[0046] Comparative Example 1

[0047] The difference between this comparative example and Example 1 is that in the modified flame retardant, MOF material, hexagonal boron nitride and polysiloxane are blended to obtain the modified flame retardant. The polysiloxane here is polydimethylsiloxane.

[0048] Comparative Example 2

[0049] The difference between this comparative example and Example 1 is that the MOF material does not include hexagonal boron nitride and phytic acid.

[0050] Comparative Example 3

[0051] The difference between this comparative example and Example 1 is that the modified flame retardant does not include polysiloxane (that is, it is not coated with polysiloxane).

[0052] Test Example 1

[0053] The samples of Examples 1-2 and Comparative Examples 1-3 were used for the test. The test indicators included: limiting oxygen index (GB / T2406.2-2009), vertical burning level (GB / T 2408-2008), tensile strength (GB / T 1040.2-2006), and impact strength (GB / T 12670-2008). The test results are shown in Table 1.

[0054] Table 1 Measurement results of each sample

[0055]

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A flame retardant waterproof coiled material, characterized in that: The raw material components are calculated by weight and include 100 parts of thermoplastic polyolefin elastomer, 20-40 parts of modified flame retardant, 5-18 parts of fiber filler, 0-3 parts of lubricant, 0-3 parts of antioxidant, 0-3 parts of stabilizer, and 0-15 parts of pigment; the modified flame retardant is based on MOF@hexagonal boron nitride@phytic acid as the core, and cross-linked polymerized polysiloxane is formed on the surface of the core.

2. The flame retardant waterproof coiled material according to claim 1, characterized in that: The fiber filler includes at least one of glass fiber and carbon fiber; and is treated with silane coupling agent KH550 when used.

3. The flame retardant waterproof coiled material according to claim 1, characterized in that: The antioxidant includes at least one of antioxidant 1010 and antioxidant 1076 .

4. The flame retardant waterproof coiled material according to claim 1, characterized in that: The stabilizer is UV531.

5. The flame retardant waterproof coiled material according to claim 1, characterized in that: The pigment includes at least one of titanium dioxide and carbon black.

6. The flame retardant waterproof coiled material according to claim 1, characterized in that: The lubricant is stearic acid or a stearate.

7. The flame retardant waterproof coiled material according to claim 1, characterized in that: The thermoplastic polyolefin elastomer comprises polyolefin and elastomer in a mass ratio of 7:

3.

8. The flame retardant waterproof coiled material according to any one of claims 1 to 7, characterized in that: The preparation method of the modified flame retardant is: In the first step, zirconium tetrachloride and 2-aminoterephthalic acid are subjected to hydrothermal reaction, and then hexagonal boron nitride is added to continue the reaction to obtain intermediate I; In the second step, the intermediate I is dispersed, phytic acid is added, and the intermediate II is obtained by treatment; In the third step, intermediate II is treated with HDTMS to obtain intermediate III; In the fourth step, after the intermediate III, octamethylcyclosiloxane, tetramethylammonium hydroxide and tetrahydrofuran are reacted, acetic acid and hexamethyldisiloxane are added to continue the reaction, and then low-boiling substances are removed by vacuum to obtain a modified flame retardant.

9. The flame retardant waterproof coiled material according to claim 8, characterized in that: The method for preparing the modified flame retardant comprises at least one of the features (1) to (4): (1) zirconium tetrachloride and 2-aminoterephthalic acid are reacted in a molar ratio of 1:1, and the mass ratio of zirconium tetrachloride to hexagonal boron nitride is 1:1; (2) The ratio of intermediate I to phytic acid is 1.5 g:5 mL; (3) The mass ratio of intermediate II to HDTMS is 1:1; (4) The mass ratio of intermediate III, methylcyclosiloxane, tetramethylammonium hydroxide, tetrahydrofuran, acetic acid and hexamethyldisiloxane is 30:100:10:5:5:

15.

10. A method for preparing a flame retardant waterproof coiled material according to any one of claims 1 to 9, characterized in that: The steps include: The raw materials are weighed in proportion, extruded and granulated by a twin-screw extruder, and then extruded, calendered, shaped and rolled to obtain a flame-retardant waterproof membrane.

Citation Information

Patent Citations

  • Anti-flaming master batch for waterproof roll and method for producing waterproof roll by anti-flaming master batch

    CN103242582A

  • Rigid flame-retardant resin composition and preparation method thereof

    CN112694673A

  • Halogen-free flame-retardant high-temperature-resistant heat-conducting polyolefin composite material as well as preparation method and application thereof

    CN115746447A

  • High-flame-retardant long-service-life thermoplastic polyolefin waterproof coiled material and preparation method thereof

    CN117659882A

  • Flame-retardant waterproof coiled material

    CN107379702A

Cited By

  • High-performance engine lubricating oil and preparation method thereof

    CN120505136A

  • Flame-retardant thermoplastic polyurethane elastomer material and preparation method thereof

    CN120758026A